2011 IEEE International Conference on Robotics and Biomimetics 2011
DOI: 10.1109/robio.2011.6181746
|View full text |Cite
|
Sign up to set email alerts
|

Artificial companion: Building a impacting relation

Abstract: In this paper we show that we are in front of an evolution from traditional human-computer interactions to a kind of intense exchange between the human user and new generation of virtual or real systems -Embodied Conversational Agents (ECAs) or affective robotsbringing the interaction to another level, the "relation level". We call these systems "companions" that is to say systems with which the user wants to build a kind of lifelong relationship.We thus argue that we need to go beyond the concepts acceptabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Pesty and Duhaut [6] defend the importance of building an "impacting relation" with artificial companions. They argue that this relation 'will enable believable interactive ECAs or robots to become believable impacting companions able to build a kind of lifelong relationship with the human'.…”
Section: Related Workmentioning
confidence: 99%
“…Pesty and Duhaut [6] defend the importance of building an "impacting relation" with artificial companions. They argue that this relation 'will enable believable interactive ECAs or robots to become believable impacting companions able to build a kind of lifelong relationship with the human'.…”
Section: Related Workmentioning
confidence: 99%
“…In previous work [16] we study long term interaction and shown that emotions and personality are important features to establish this long relation. In this paper we want to go farther and discuss the set of dimensions to take into account to build an acceptable artificial companion.…”
Section: To Cite This Versionmentioning
confidence: 99%
“…These systems can be virtual, Embodied Conversational Agents (ECAs), or real systems robots. We call these systems "artificial companions" that is to say systems with which the user wants to build a kind of life-long relationship.In previous work [16] we study long term interaction and shown that emotions and personality are important features to establish this long relation. In this paper we want to go farther and discuss the set of dimensions to take into account to build an acceptable artificial companion.…”
mentioning
confidence: 99%
“…The question is to know how to create such a game in order to maximize its impact [11]. The game we built is guided by users.…”
Section: Introductionmentioning
confidence: 99%